Theory, implementation, and simulated examples of a Maximum-Likelihood Parameter-Estimation algorithm for state-space systems with coloured measurement noise - Eglington, Michael Lyle (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1994.